2024
DOI: 10.1073/pnas.2311885121
|View full text |Cite
|
Sign up to set email alerts
|

Neural heterogeneity controls computations in spiking neural networks

Richard Gast,
Sara A. Solla,
Ann Kennedy

Abstract: The brain is composed of complex networks of interacting neurons that express considerable heterogeneity in their physiology and spiking characteristics. How does this neural heterogeneity influence macroscopic neural dynamics, and how might it contribute to neural computation? In this work, we use a mean-field model to investigate computation in heterogeneous neural networks, by studying how the heterogeneity of cell spiking thresholds affects three key computational functions of a neural population: the gati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 97 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…The heterogeneity of neuron properties has received much interest lately: for instance, it has been shown that heterogeneity in neural populations can increase coding robustness and efficiency [ 48 ], help optimize information transmission [ 80 ], increase network responsiveness [ 81 ], promote robust learning [ 82 ], help to control the dynamic repertoire of neural populations [ 83 ] and improve the performance on several tasks [ 84 , 85 ]. Here, we show that in particular, the population of excitatory neurons of the barrel cortex shows a large variability in their intrinsic and response properties.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The heterogeneity of neuron properties has received much interest lately: for instance, it has been shown that heterogeneity in neural populations can increase coding robustness and efficiency [ 48 ], help optimize information transmission [ 80 ], increase network responsiveness [ 81 ], promote robust learning [ 82 ], help to control the dynamic repertoire of neural populations [ 83 ] and improve the performance on several tasks [ 84 , 85 ]. Here, we show that in particular, the population of excitatory neurons of the barrel cortex shows a large variability in their intrinsic and response properties.…”
Section: Conclusion and Discussionmentioning
confidence: 99%